ANALISIS FUNGSI KONJUNGSI SHIKAMO DAN SONOUE SERTA PADANANNYA DALAM BAHASA INDONESIA - Tri Endang Vadilah; Arza Aibonotika; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study examines the functions of Japanese shikamo and sonoue conjunctions and their equivalents in Indonesian. This study aims to explain the differences and similarities in the use of shikamo and sonoue. To explain the differences and similarities, a literature review is conducted and translational methods are used to match them. Based on the results of the analysis it was found that the function of the shikamo conjunction is a conjunction used to connect sentences equivalent to adding details of the assertion, both subjectivity and objectivity of the speaker in reinforcing things unexpectedly accompanied by propositions in them. These uses can be paired with forms {and more, moreover, and, besides, even, in addition, in addition, after all, moreover, likewise, then, then, afterwards, furthermore, additionally, in fact, that, in fact, in fact, even, even so, even though even so, even though, even so, but and yet in Indonesian. Whereas the sonoue conjunction function is a conjunction used to link the addition of details as a condition, affirmation statement, speaker subjectivity with propositions in the conclusions and statements of continuation of the clauses or sentences conveyed earlier. In the uses it can be paired with forms {other than that, and again, in addition, even, moreover, before that, then, after that, after that, then, then, then that, so, therefore, therefore, by therefore, therefore, therefore, thus, in this way, in fact, instead, and, as well as, but, and yet} in Indonesian. Key Words: Conjunction, Shikamo, Sonoue, Equivalent